Lead (Pb) Toxicity; Physio-Biochemical Mechanisms, Grain Yield, Quality, and Pb Distribution Proportions in Scented Rice - Ashraf, Umair; Kanu, Adam S.; Deng, Quanquan; Mo, Zhaowen; Pan, Shenggang; Tian, Hua; Tang, Xiangru (Frontiers in Plant Science, 2017)
Lead (Pb) caused interruptions with normal plant metabolism, crop yield losses and quality issues are of great concern. This study assessed the physio-biochemical responses, yield and grain quality traits and Pb distribution proportions in three different fragrant rice cultivars i.e., Meixiangzhan-2, Xinagyaxiangzhan and Basmati-385. Plants were exposed to 400, 800, and 1200 ppm of Pb while pots without Pb were taken as control (0 ppm). Our results showed that Pb toxicity significantly (P<0.05) reduced photosynthetic pigments (chlorophyll contents and carotenoids) and inducted oxidative stress with increased production of hydrogen peroxide (H2O2), malanodialdehyde (MDA) and leaves leachates; while such effects were more apparent in Xinagyaxiangzhan than other two rice cultivars. Pb stress differentially affected the production protein, proline and soluble sugars; however the production rates were higher at heading stage (HS) than maturity stage (MS). Furthermore, Pb stress altered superoxide dismutase (SOD), peroxidases (POD), catalases (CAT) and ascorbate peroxidases (APX) activities and glutathione (GSH) and oxidized glutathione (GSSG) production in all rice cultivars at both HS and MS. All Pb levels reduced the yield and yield components of all rice cultivars; nonetheless such reductions were observed highest in Xinagyaxiangzhan (69.12%) than Meixiangzhan-2 (58.05%) and Basmati-385 (46.27%) and resulted in grain quality deterioration. Significant and positive correlations among rice yields with productive tillers/pot and grains per panicle while negative with sterility percentage were also observed. In addition, all rice cultivars readily taken up the Pb contents from soil to roots and transported upward in different proportions with maximum in roots followed by shoots, leaves, ears and grains. Higher proportions of Pb contents in above ground plant parts in Xinagyaxiangzhan possibly lead to maximum losses in this cultivar than other two cultivars; while less damage in Basmati-385 might be related to strong anti-oxidative defence system and lower proportions of Pb contents in its aerial parts.